2017
DOI: 10.1002/jrs.5179
|View full text |Cite
|
Sign up to set email alerts
|

Laser perturbation two‐dimensional correlation Raman spectroscopy for quality control of bovine colostrum products

Abstract: In this paper, laser perturbation two‐dimensional correlation Raman spectroscopy was explored as a rapid and reliable determination method for the assessment of bovine colostrum products and their analogue, namely, milk powder. Compared with the traditional instrumental analytical methods, such as chromatography, Raman spectroscopy measurements can be realized easily without the need of sample preparation. Two‐dimensional correlation spectroscopy can enhance the spectral resolution and provide more useful info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The Raman spectra of dairy products are shown in Figure 1. The main vibrational bands are assigned as follows according to the previous reports (McGoverin et al, 2010;Almeida et al, 2011;Mazurek et al, 2015;Júnior et al, 2016;Zhang et al, 2017c). The Raman band at 1,752 cm −1 could be attributed to the C=O stretching ester of fatty acids.…”
Section: Raman Spectroscopic Analysis Of Dairy Productsmentioning
confidence: 93%
“…The Raman spectra of dairy products are shown in Figure 1. The main vibrational bands are assigned as follows according to the previous reports (McGoverin et al, 2010;Almeida et al, 2011;Mazurek et al, 2015;Júnior et al, 2016;Zhang et al, 2017c). The Raman band at 1,752 cm −1 could be attributed to the C=O stretching ester of fatty acids.…”
Section: Raman Spectroscopic Analysis Of Dairy Productsmentioning
confidence: 93%
“…Their results showed that the correlation coefficients between each bovine colostrum product with their mean value 0.991 ± 0.003, which indicated that there were high similarities between these products. Under the same experimental conditions the correlation coefficients between the bovine colostrum product (mean) and the other brands of milk powder that include bovine colostrum products containing some milk powder were located in the range of 0.596–0.761, far below the value of 0.991 ± 0.003 …”
Section: Pharmaceutical Food and Forensic Applicationsmentioning
confidence: 99%
“…Under the same experimental conditions the correlation coefficients between the bovine colostrum product (mean) and the other brands of milk powder that include bovine colostrum products containing some milk powder were located in the range of 0.596-0.761, far below the value of 0.991 ± 0.003. [200] 18 | HIGH PRESSURE AND TEMPERATURE STUDIES Capitani et al studied the pressurizing of the mixtures of two ionic liquids to decide between crystallization versus vitrification. They suggest that disorder, induced by the high number of possible configurations for the long alkyl chain in a compressed environment, is a key factor in the suppression of the crystallization process.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%
“…Second, it is recently reported that some "counterfeit" products are all qualified products in fact, which will not cause harm to human body but are illegally used by criminals to pretend to be high-quality products. In this way, illegal profits can be obtained [6].…”
Section: Introductionmentioning
confidence: 99%